2013
DOI: 10.1074/jbc.m113.504928
|View full text |Cite
|
Sign up to set email alerts
|

RhoG Protein Regulates Glycoprotein VI-Fc Receptor γ-Chain Complex-mediated Platelet Activation and Thrombus Formation

Abstract: Background: RhoG is a ubiquitously expressed member of the Rho family of GTPases. Results: RhoG-deficient platelets display severely impaired GPVI-dependent platelet activation. Conclusion: RhoG plays an important role in GPVI-FcR␥ complex-mediated platelet activation and thrombus formation. Significance: Our study enhances the understanding of the molecular mechanisms of GPVI-FcR␥ complex activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 52 publications
1
26
0
1
Order By: Relevance
“…2 PAR-1 activating peptide SFLLRN and PAR-4 activating peptide AYPGKF activate both G q and G 12/13 pathways, leading to a calcium-dependent and calcium-independent shape change and platelet aggregation. As generally recognized, 10 μM SFLLRN or 100 μM AYPGKF caused full platelet aggregation 36 (►Fig. 1A,B); at 50 nM, the Gq inhibitor YM-254890 also abolished platelet aggregation induced by AYPGKF and SFLLRN.…”
Section: Combined Gi and G 12/13 Signaling Induces Human Platelet Aggsupporting
confidence: 63%
“…2 PAR-1 activating peptide SFLLRN and PAR-4 activating peptide AYPGKF activate both G q and G 12/13 pathways, leading to a calcium-dependent and calcium-independent shape change and platelet aggregation. As generally recognized, 10 μM SFLLRN or 100 μM AYPGKF caused full platelet aggregation 36 (►Fig. 1A,B); at 50 nM, the Gq inhibitor YM-254890 also abolished platelet aggregation induced by AYPGKF and SFLLRN.…”
Section: Combined Gi and G 12/13 Signaling Induces Human Platelet Aggsupporting
confidence: 63%
“…NK cells can also induce allograft injury via direct mechanisms (antibody-dependent cell-mediated cytotoxicity) and indirect mechanisms (cytokine production to activate other leucocytes) (Rocha et al 2003;Murata & Baldwin 2009). Syk is required for platelet activation and thrombosis via glycoprotein VI-FccR-mediated signalling (Kim et al 2013;Ozaki et al 2013), and Syk inhibitor treatment has been shown to suppress thrombosis and renal injury in antibody-dependent native kidney disease (Ryan et al 2011). Finally, thrombosis is an important mechanism of allograft injury (Meehan et al 2003;Murata & Baldwin 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, thrombosis is an important mechanism of allograft injury (Meehan et al 2003;Murata & Baldwin 2009). Syk is required for platelet activation and thrombosis via glycoprotein VI-FccR-mediated signalling (Kim et al 2013;Ozaki et al 2013), and Syk inhibitor treatment has been shown to suppress thrombosis and renal injury in antibody-dependent native kidney disease (Ryan et al 2011). Thus, inhibition of platelet activation may also have contributed to the reduction in capillary thrombosis seen with CC0482417 treatment of renal allografts.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were performed as described previously [25]. Adult mice (aged 10-12 weeks) were anesthetized by intraperitoneal injection of pentobarbital (40 mg kg À1 ), and FeCl 3 -induced thrombosis was assessed as described previously [30].…”
Section: Platelet Spreading and Clot Retractionmentioning
confidence: 99%